2006
DOI: 10.1063/1.2191628
|View full text |Cite
|
Sign up to set email alerts
|

Plasma oscillations in high-electron-mobility transistors with recessed gate

Abstract: We calculate the plasma oscillation spectrum in high-electron-mobility transistors (HEMTs) with recessed gate having the highly doped caps adjacent to the source and drain contacts and the windows between the caps and the gate. The resonant plasma frequencies are found as functions of the lengths of the gate, cap, and window regions, the electron concentration in the transistor channel, and the gate voltage. We demonstrate that the effect of cap region can result in a significant reduction of the resonant freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…The transistor consists not only of the gated part but also of the ungated part that is covered by the cap layer. As predicted in [13], the cap regions significantly affect the plasma oscillation spectrum in HEMTs: the resonant plasma frequencies dramatically decrease with increasing cap region length. In order to take into account the effect of such cap layers, a correction to Eq.…”
Section: Resultsmentioning
confidence: 84%
“…The transistor consists not only of the gated part but also of the ungated part that is covered by the cap layer. As predicted in [13], the cap regions significantly affect the plasma oscillation spectrum in HEMTs: the resonant plasma frequencies dramatically decrease with increasing cap region length. In order to take into account the effect of such cap layers, a correction to Eq.…”
Section: Resultsmentioning
confidence: 84%
“…Σ 0 being the so-called "fictituous" effective hole (electron) mass in graphene layers [27], ν = (σ B,ω /W E C g ) and ν = 1/τ +ν, where τ is the hole momentum relaxation time in the 2DHG andν =ν visc +ν rad is associated with the contribution of the 2DHG viscosity to the damping (see for example, Ref. [21]) and with the radiation damping of the plasma oscillations.…”
Section: Plasma Oscillations and Rectified Currentmentioning
confidence: 99%
“…The detector responsivity R ω ∝ δJ C,ω /|δV ω | 2 . Due to the possibility of the plasmonic resonances, the rectified component (the detector output signal) can be resonantly large, similar to that in the HET detector [21] and other plasmonic THz detectors using different transistor structures, including those incorporating graphene [22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The antenna, placed at the focal point of the parabolic mirror, quasioptically collects the terahertz signalleading to superior performance. Ryzhii et al, [Ryzhii et al, 2006] investigated the plasma oscillations in a two-dimensional electron channel with a reverse-biased Schottky junction. They show that the plasma instability can be used in a novel diode device -lateral Schottky junction tunneling transit-time terahertz oscillator.…”
Section: Schottky Barrier Detectorsmentioning
confidence: 99%
“…They have showed that these transistors are tunable by the gate voltage between 0.75 and 2.1 THz. It is also possible to tune operating frequency by manipulating cap, window, and gate lengths and other structural parameters [Ryzhii et al, 2006].…”
Section: High Electron Mobility Transistor Detectorsmentioning
confidence: 99%